Career Trajectories of Deputy and Assistant Headteachers and Their Perceptions of Secondary Headship. Issue 2 (April 2019) - Bruce-Golding, Judith
Currently, the United Kingdom is experiencing an "education workforce and leadership crisis, " which spans from the beginnings of the teaching career to the higher echelons of senior leadership. The purpose of this study is to investigate the career trajectories and experiences of Deputy and Assistant Headteachers in Birmingham, England. This article draws from an original thesis and presents the findings from a narrative study on the career trajectories of 14 Deputy and Assistant Headteachers in Birmingham, England. The findings from this study add new insights to the senior leadership role and the perception of Headship in that the Deputy and Assistant Headteacher career stage and socialisation experiences can determine whether they stay, leave, or climb the career ladder to Headship. This article suggests that Deputy and Assistant Headteachers lean toward displaying mainly Bonder, Bridger, or Leaver characteristics that contribute to aspiration and how they utilize their social capital in their career journeys. A new career stages and phases framework pertaining to Deputy and Assistant Headship in secondary schools has been forwarded which draws types of social capital.